ANALISIS PROGRAM PEMBERDAYAAN DAN KESEJAHTERAAN KELUARGA (PKK) DALAM UPAYA PENINGKATAN KESEJAHTERAAN EKONOMI WARGA DI KELURAHAN SIDORAME TIMUR KOTA MEDAN - Anshar, M. (Universitas Dharmawangsa, 2025)
This study aims to analyze more about the family welfare program, This is because the family is the smallest unit of society that will have a big impact on the performance development in support of government programs. Of a prosperous family, then governance of national and state will be able to give birth of peace, security, harmony, and peace. Thus, the welfare of the family became one of the explanations in development by government programs. The research was conducted in the village of Sei ape Downstream II Medan. This research is a qualitative descriptive study with the object of PKK cadres along with village residents Sidorame Timur City field. Primary Data in Obtains through interviews and secondary data obtained from the literature. The results of the study explains that